2003
DOI: 10.1038/sj.eye.6700586
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of diabetic retinopathy

Abstract: Eye (2003) 17, 550-562.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The possibility of an effect of statins has been investigated over the last 10 years with early encouraging results in small studies of macular oedema and exudates. 24 Larger studies of statins for example CARDS, 25 which included 2838 patients over a median follow-up of 3.9 years, showed that atorvostatin 10 mg daily resulted in a trend to reduction of laser therapy compared with placebo, but no influence on diabetic retinopathy progression. Thus, the influence of statins on diabetic retinopathy continues to be debated and better evidence on the effects of larger doses of statins are required but, if there is an effect of statins, it is likely to be small.…”
Section: Statins and Fibratesmentioning
confidence: 99%
“…The possibility of an effect of statins has been investigated over the last 10 years with early encouraging results in small studies of macular oedema and exudates. 24 Larger studies of statins for example CARDS, 25 which included 2838 patients over a median follow-up of 3.9 years, showed that atorvostatin 10 mg daily resulted in a trend to reduction of laser therapy compared with placebo, but no influence on diabetic retinopathy progression. Thus, the influence of statins on diabetic retinopathy continues to be debated and better evidence on the effects of larger doses of statins are required but, if there is an effect of statins, it is likely to be small.…”
Section: Statins and Fibratesmentioning
confidence: 99%
“…However, further investigation is underway with two large prospective randomised controlled trials, ASPEN and the CARDS study, due to report later in 2004. 7,17,18 The CARDS study will support more widespread statin prescription in type II diabetic patients, and if the conclusions from this study are correct we may in turn see a delay or reduction in the episodes of preretinal or vitreous haemorrhage in diabetic patients.…”
Section: Discussionmentioning
confidence: 73%
“…9 In addition, there is limited evidence that statins may reduce retinal exudation in patients with diabetic maculopathy, an effect to be confirmed in ongoing large randomised clinical trials. 15,16 This study has demonstrated that there is still much input required to achieve optimal metabolic and BP control to delay progression and need for laser treatment of DR. In view of the above findings, we feel that ophthalmologists responsible for the care of patients with DR should ensure that the patients receive both adequate medical therapies to optimise glycaemic and BP control, as well as laser photocoagulation.…”
Section: Discussionmentioning
confidence: 98%